Introducing Three New Fruit-Scented Mints to Farmlands: Insights on Drug Yield, Essential-Oil Quality, and Antioxidant Properties - Hosein Ahmadi; Mohammad Reza Morshedloo; Roya Emrahi; Abdollah Javanmard; Farzad Rasouli; Filippo Maggi; Manoj Kumar; Jose Manuel Lorenzo (Antioxidants, 2022)
Mint species are one of the most traded medicinal plants with a wide array of applications in the food, pharmaceutical, and perfumery industries. Here, a field experiment based on completely randomized block design (RCBD) aimed to compare drug yield, antioxidant properties, and essential-oil (EO) quality of three newly introduced mints (i.e., ginger mint, pineapple mint, and grapefruit mint) with a chiefly cultivated one (i.e., peppermint). The results manifested that dry-weight yield and EO yield of grapefruit mint (310 g/m2 and 5.18 g/m2, respectively) was approximately 2 times more than that of others. The highest EO content (i.e., 3.12%, v/w)) was obtained from the ginger mint; however, there were no significant differences among the other three mints. The highest total flavonoids content and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity of both methanolic and ethanolic extracts were found in pineapple and grapefruit mint. Methanolic extract of ginger mint yielded the highest total polyphenol content, whereas the ethanolic extract of pineapple mint showed the highest total polyphenol content. According to mean comparisons, the EO of ginger mint exhibited the highest antioxidant activity (EC50 value = 2.23 µL/mL), while EO of peppermint showed the lowest antioxidant activity (EC50 value = 48.23 µL/mL). Gas chromatography analysis identified four EO types among these mints: (i) grapefruit mint EO rich in linalool (51.7%) and linalyl acetate (28.38%); (ii) ginger mint EO rich in linalool (59.16%); (iii) pineapple mint EO rich in piperitone oxide (77.65%); and (iv) peppermint EO rich in menthol (35.65%). The findings of the present study provide new insights into the cultivation of preferable mints possessing desired characteristics for food and drug industries.